Biomechanical Comparison of Anatomic Versus Lower of Anteromedial and Anterolateral Tibial Tunnels in Posterior Cruciate Ligament Reconstruction. Issue 3 (4th January 2023) - Peng, Bo; Tang, Yuchen; Jia, Gengxin; Geng, Bin; Xu, Lihu; Xia, Yayi; Teng, Yuanjun
Abstract : Objective: In order to reduce the "killer turn" effect, various tibial tunnels have been developed. However, few studies investigated the biomechanical effects of different tibial tunnels during PCL reconstruction. This study aims to compare the time‐zero biomechanical properties of anteromedial, anterolateral, lower anteromedial, and lower anterolateral tibial tunnels in transtibial posterior cruciate ligament (PCL) reconstruction under load‐to‐failure loading. Methods: Porcine tibias and bovine extensor tendons were used to simulate in vitro transtibial PCL reconstruction. Forty bovine extensor tendons and 40 porcine tibias were randomly divided into four experimental groups: anteromedial tunnel group (AM group, n  = 10), anterolateral tunnel group (AL group, n  = 10), lower anteromedial tunnel group (L‐AM group, n  = 10), and lower anterolateral tunnel group (L‐AL group, n  = 10). The biomechanical test was then carried out in each group using the load‐to‐failure test. The ultimate load (in newtons), yield load (in newtons), tensile stiffness (in newtons per millimeter), load‐elongation curve, failure mode, and tibial tunnel length (in millimeter) were recorded for each specimen. One‐way analysis of variance (ANOVA) was used to compare the mean differences among the four groups. Results: The biomechanical outcomes showed that there were no differences in the mean tensile stiffness and failure mode among four groups. The ultimate load and yield load of the L‐AM group were significantly higher than those of other three groups ( P  < 0.05). For the AM group, its ultimate load is significantly higher than that of the L‐AL group ( P  < 0.05), and its yield load is higher than that of the AL group and L‐AL group ( P  < 0.05). However, we found no significant differences in either ultimate load or yield load between AL group and L‐AL group ( P  > 0.05). There was significant statistical difference in the length of tibial tunnel between anatomic groups (AM and AL) and lower groups (L‐AM and L‐AL) ( P  < 0.05). Conclusion: Compared with the anteromedial, anterolateral, and lower anterolateral tibial tunnel, the lower anteromedial tibial tunnel showed better time‐zero biomechanical properties including ultimate load and yield load in transtibial PCL reconstruction. Abstract : Schematic of different tibial tunnel placement. Yellow tunnel: AM tibial tunnel; red tunnel: L‐AM tibial tunnel; green tunnel: AL tibial tunnel; black tunnel: L‐AL tibial tunnel.